1996
DOI: 10.1111/j.1540-8191.1996.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Anatomy of Ventricular Septal Defect Part IV: Double Outlet Ventricle

Abstract: In this fourth part of our series of articles concerned with the surgical anatomy of ventricular septal defects (VSDs), we have analyzed the arrangements when both arterial trunks arise from the same ventricle. The essence of these anomalies is that the interventricular communication is an integral part of the circulation. Unless the surgeon constructs an alternative route of exit, closure of this defect would isolate one of the ventricles. The usual surgical approach, therefore, is to patch the hole between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
(5 reference statements)
1
6
0
Order By: Relevance
“…From the point of view of a surgeon, the high frequency of the infundibular and mixed type of obstruction of RVOT obstruction in these groups, is of interest to the anatomy of the coronary arteries in this area [12]. Wilcox B. R. et al subdivided abnormalities of the CA observed in these patients into 3 variants [13]. Table 6 presents variants of abnormalities of the coronary arteries, which were found in our study.…”
Section: вісник серцево-судинної хірургії 2018supporting
confidence: 51%
“…From the point of view of a surgeon, the high frequency of the infundibular and mixed type of obstruction of RVOT obstruction in these groups, is of interest to the anatomy of the coronary arteries in this area [12]. Wilcox B. R. et al subdivided abnormalities of the CA observed in these patients into 3 variants [13]. Table 6 presents variants of abnormalities of the coronary arteries, which were found in our study.…”
Section: вісник серцево-судинної хірургії 2018supporting
confidence: 51%
“…It is useful to unify hearts with double outlet right ventricle on the basis of the orientation of the ventricular septal defect relative to the great arteries, and this approach has unequivocal surgical relevance. 4,5 Within and between these subsets, nonetheless, there remains a morphologic spectrum. 6 It is not always very easy to distinguish one pattern from another, such as the subaortic defect from the doubly-committed one, or the subaortic from the non-committed defect.…”
Section: Discussionmentioning
confidence: 99%
“…• In the presence of a double-outlet ventricle, when both great arteries arise from the same ventricle, interventricular communication via the VSD is an integral part of the circulation [ 16 ]. Closure of the VSD will isolate one ventricle, and the surgeon must create an alternate outfl ow tract for that ventricle [ 16 ].…”
Section: Managementmentioning
confidence: 99%
“…Closure of the VSD will isolate one ventricle, and the surgeon must create an alternate outfl ow tract for that ventricle [ 16 ]. A DOLV with two well-developed ventricles and pulmonary stenosis is conventionally treated surgically by VSD closure, closure of the native left ventricle-to-pulmonary outfl ow and placement of a right ventricle-to-pulmonary artery extracardiac conduit (Rastelli repair).…”
Section: Managementmentioning
confidence: 99%